The Case for a Socially Oriented Business Model Canvas: The Social Enterprise Model Canvas. Issue 2 (4th May 2019) - Sparviero, Sergio
Abstract: The main purpose of this article is to introduce the Social Enterprise Model Canvas (SEMC), a Business Model Canvas (BMC) conceived for designing the organizational settings of social enterprises, for resolving the mission measurement paradox, and for meeting the strategy, legitimacy and governance challenges. The SEMC and the analysis that explains its features are of interest to academics concerned with the study of social entrepreneurship because they offer a new analytical tool that is particularly useful for untangling and comparing different forms of social enterprises. Also, it is of interest to social entrepreneurs, because the SEMC is a platform that can be used to prevent 'mission drifts' that might result from problems emerging from the mismanagement of such challenges. The arguments presented are grounded on scientific literature from multiple disciplines and fields, on a critical review of the BMC, and on a case study. The main features of SEMC that makes it an alternative to the BMC are attention to social value and building blocks that take into consideration non-targeted stakeholders, principles of governance, the involvement of customers and targeted beneficiaries, mission values, short-term objectives, impact and output measures.